Quality enhancement in Madrasa education an exploratory study - Basheer, K. Mohammed (Cambridge Scholars Publishing, 2016)
This unique empirical study focuses on the different quality dimensions of the Madrasa education system in Kerala, southwestern India. Madrasa education is one of the largest networks of non-governmental organisations (NGOs) in the world. Despite originating several centuries ago in a vastly different social and cultural context, it continues to address the educational needs of a large section of the Muslim population in India. Although the Madrasa system has seen many significant developments over time, academia has not paid much attention to its functions, strengths and contributions. This study fills this lacuna, and is grounded in detailed empirical investigation based on ethnographic surveys and interviews with various stakeholders from the field comprising students, teachers, parents, management committees, Madrasa boards and educationists."--Dust jacket.